La relación entre el burnout y el work engagement en trabajadores de salud - Castillo Brescia, Sebastián (2022)
Engagement is an affective-cognitive, positive and lasting state related to job performance; on the other hand, burnout is a prolonged response to stressful elements in various contexts. Due to the opposite relationship between both constructs, the objective of this study is to identify whether work engagement can be a protective factor against burnout syndrome. For this, a systematic search was carried out following the indications of the Prisma guide (Urrútia and Bonfill, 2013), where the databases consulted were Scopus, APA PsycNET, Psicodoc, Springer, Ebsco and Proquest. Sixteen articles were selected, taking into consideration the established inclusion criteria, some of these criteria were that the articles should correlate the variables to be studied in populations of health personnel, as well as, they should come from the science of psychology due to their presence in indexed journals of psychology or because they were written by psychologists. It was obtained as a result that engagement can act as a protective factor; however, it is not definitive, since there are other variables that intervene in this relationship.